Keputusan Siswa Memilih SMK Swasta di Kota Bandung - Setiawan, adang (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
Implementation of the Service Marketing Mix Implementation in order to improve performance is expected to be a strength of the school so that the school becomes the choice of the community. The results of the research show that the implementation of the marketing mix of services consisting of products, prices, promotions, places, people / human resources, physical evidence, customer processes and services partially has a significant effect on student decisions, and simultaneously has a significant effect on the decisions of students choosing Private Vocational Schools Bandung. The most dominant variable is the factor of the location of the school, while the influence simultaneously is the decision of students so that other influences are influenced by other factors that need to be further investigated.